Effect of dietary threonine level on productivity and carcass characteristics of Ross 308 broiler chickens - Ngomani, Delisile (University of Limpopo, 2019)
Two experiments were conducted to determine the effect of dietary threonine level on production performance and carcass characteristics of Ross 308 broiler chickens. In each experiment the diets were isocaloric and isonitrogenous but with different dietary threonine levels.The first part of the study determined the effect of dietary threonine level on feed intake, growth rate, mortality and carcass characteristics of Ross 308 broiler chickens aged between Day 1-21. A total of 150 unsexed day-old chicks were used in a complete randomized design having 5 treatments (6.4, 7.5, 8, 8.5 and 9g of threonine/kg DM feed), replicated three times and having ten chickens per replicate. The second part of the study determined the effect of dietary threonine level on feed intake, digestibility, growth rate, mortality and carcass characteristics of male Ross 308 broiler chickens aged between Day 22-42. Seventy-five male chickens were used in a complete randomized design having 5 treatments (6.4, 7.5, 8, 8.5 and 9g of threonine/kg DM feed), replicated three times and having five chickens per replicate. A quadratic regression model was used to determine the optimal productivity of the chickens while a General Linear Model (GLM) procedures for the statistical analysis of variance was used to detect dietary treatment effects. Where there were significant differences (P<0.05), Turkey’s honestly significant difference test (HSD) was used for mean separation. The chickens were slaughtered at the ages of 21 and 42 days for Experiments 1 and 2, respectively, following ethical standards as recommended by the University of Limpopo Animal Research Ethics Committee (AREC/12/2017: PG). Two chickens per replicate for both studies were slaughtered for the determination of carcass characteristics (carcass and organ weights, gut organ digesta pH and gastro-intestinal length measurements). Dietary threonine levels used in this experiment affected (P<0.05) feed intake, growth rate, live weight, metabolisable energy (ME) intake, nitrogen retention, feed conversion ratio and gut organ weights and lengths of unsexed Ross 308 broiler chickens aged 21 days. Dietary threonine level did not affect (P>0.05) diet digestibility. Feed conversion ratio, pH of the proventriculus digesta, gut intestine length and caecum length of unsexed broiler chickens were optimized at different dietary threonine levels of 9.6, 8.5, 6.6 and 8.4 g/kg DM, respectively. Dietary threonine levels had an effect (P<0.05) on feed intake, diet digestibility, metabolizable energy, live weight, proventriculus pH values, GIT length, gut organ and carcass organ weights of male Ross 308 broiler chickens between 22 to 42 days of age. Proventriculus and large intestine weights were optimized at different dietary threonine levels of 7.5 and 9.1 g/kg DM feed, respectively. Dietary threonine level did not affect (P>0.05) growth rate, feed conversion ratio of male Ross 308 broiler chickens between 22 to 42 days of age. It is concluded that dietary threonine levels used in this study affected production performance of younger broilers (Day 1-21) more than that of older birds (Day 22-42). However, production variables were optimized at different dietary threonine levels. This has implication on diet formulation for the chickens and no linear response could be established
Thesis (M.Sc. (Animal Production)) --University of Limpopo, 2019
Keywords: Feed intake; Growth rate; Feed conversion ratio; Live weight; Carcass characteristics; Threonine; Broiler chickens; Broilers (Chickens).; Chicken industry